Using a Research Domain Ontology as a driver for Technology Commercialization - Júlio António Bandeira Girão (2021)
The Operator 4.0 concept plays a key role in the kind of industry we find ourselves in today, Industry 4.0. In the course of the literature review, it became evident that there was an absence of a reference model to support the development of innovative concepts for Operator 4.0. Therefore, this research will focus on its development, in partnership with Fraunhofer Portugal Research Center for Assistive Information and Communication Solutions - Fraunhofer AICOS. As a result, an ontology was created, and Design Science Approach used to help its development, followed by a first validation by Fraunhofer Portugal experts. A Focus Group session was held with experts from Fraunhofer Portugal, who participated in the validation of the ontology as well as the evaluation of the competence questions, as a final validation. This study contributed to a better understanding of how knowledge organization (Frishammar, Lichtenthaler, & Rundquist, 2012) in a given technological domain might assist in decision making when a new research project is proposed that may result in future intellectual property. This intellectual property would be licensed or exploited in some way in the future. Following the ontology validation, a workshop was held to demonstrate the second contribution of this dissertation, a proposal on how to use the ontology as a driver to start the technology process in the context of identifying opportunities for future commercialization of the technology. In the end, this study answered the research question and related competence questions. Therefore, it can be said that with this research, a reference model has been effectively developed to support the construction of Operator 4.0 solutions for industry.